2018
DOI: 10.1101/364679
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

NHA2 promotes cyst development in an in vitro model of polycystic kidney disease

Abstract: Key pointsr Significant and selective up-regulation of the Na + /H + exchanger NHA2 (SLC9B2) was observed in cysts of patients with autosomal dominant polycystic kidney disease.r Using the MDCK cell model of cystogenesis, it was found that NHA2 increases cyst size.Silencing or pharmacological inhibition of NHA2 inhibits cyst formation in vitro.r Polycystin-1 represses NHA2 expression via Ca 2+ /NFAT signalling whereas the dominant negative membrane-anchored C-terminal fragment (PC1-MAT) increased NHA2 levels.r… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 74 publications
(113 reference statements)
0
5
0
Order By: Relevance
“…Using a wellrecognized in vitro model of cyst formation involving the growth of MDCK hemicysts/domes in culture, they demonstrated that both the transport inhibitor phloretin and shRNA-mediated knockdown of NHA2 markedly reduced cyst size. Prasad et al (2019) present strong evidence for the involvement of NHA2 as a novel acid-base transporter in ADPKD. NHA2 expression was closely associated with well-established ADPKD mechanisms and signalling pathways (e.g.…”
mentioning
confidence: 61%
See 3 more Smart Citations
“…Using a wellrecognized in vitro model of cyst formation involving the growth of MDCK hemicysts/domes in culture, they demonstrated that both the transport inhibitor phloretin and shRNA-mediated knockdown of NHA2 markedly reduced cyst size. Prasad et al (2019) present strong evidence for the involvement of NHA2 as a novel acid-base transporter in ADPKD. NHA2 expression was closely associated with well-established ADPKD mechanisms and signalling pathways (e.g.…”
mentioning
confidence: 61%
“…In the current issue of The Journal of Physiology, Prasad et al (2019) have further explored the involvement of acid-base transporters in PKD. The authors report that the human NHA2 orthologue of the bacterial NhaA (NHE superfamily) is upregulated in human ADPKD, and NHA2 stimulates cyst growth in an in vitro cell model.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…In 2021, Anderegg et al corroborated the NHA2 role in blood pressure regulation in mice, and identified it as critical for the maintenance of serine–threonine with‐no‐lysine kinase 4 (WNK4) levels, and thus ultimately for the activity of the Na + /Cl − co‐transporter NCC in the distal convoluted tubules of the kidney 12 . Increased NHA2 expression also promotes cyst development in an in vitro model of polycystic kidney disease 13 . In the testis, NHA2 is relevant for sperm motility and male fertility, since the deletion of NHA2 significantly reduced the percentage of motile sperm (of about 30%) and resulted in a decrease in pregnancy rate (of about 25%) in mice 14 .…”
Section: Introductionmentioning
confidence: 99%